2022
DOI: 10.1177/00220221221132778
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Preferred Recovery Pathways Among Urban American Indians and Alaska Natives Experiencing Alcohol Use Disorders

Abstract: Approximately three fourths of the American Indian and Alaska Native (AI/AN) population lives in urban areas, and urban AI/ANs are disproportionately affected by alcohol-related morbidity and mortality. Although no studies have documented alcohol use disorder (AUD) treatment outcomes specific to urban AI/ANs, studies in other Native communities highlight concerns about the cultural acceptability of directive, abstinence-based approaches, such as cognitive behavioral therapy and 12-step programs. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…That said, quantitative and qualitative research has indicated that many of these sufferers will simply not present for abstinence-based treatment, even when facing external coercion (Center for Behavioral Health Statistics and Quality, 2022; SAMHSA, 2019). Alternatively, they may attend but are turned away by providers due to intoxication, or can't engage authentically in treatment programming that requires commitment to abstinence, will leave treatment early, and/or complete treatment but relapse shortly thereafter (Collins et al, 2012(Collins et al, , 2016Crabtree et al, 2018;Nelson et al, 2023;Orwin et al, 1999), compounding medical risks such as the worsening "kindling effect" observed in the case of alcohol withdrawal (Becker, 1998). In contrast, for those providers who work primarily with nontreatment-seekers who are severely impacted by substance-related harm (e.g., people experiencing homelessness in community-based settings such as shelters), only 5% of whom are interested in abstinence (Fentress et al, 2021), providers must partner with these potential service users ("meet them where they are at") if they hope to be helpful.…”
Section: Limitations On Integrating the Constructs Of Substitute Addi...mentioning
confidence: 99%
“…That said, quantitative and qualitative research has indicated that many of these sufferers will simply not present for abstinence-based treatment, even when facing external coercion (Center for Behavioral Health Statistics and Quality, 2022; SAMHSA, 2019). Alternatively, they may attend but are turned away by providers due to intoxication, or can't engage authentically in treatment programming that requires commitment to abstinence, will leave treatment early, and/or complete treatment but relapse shortly thereafter (Collins et al, 2012(Collins et al, , 2016Crabtree et al, 2018;Nelson et al, 2023;Orwin et al, 1999), compounding medical risks such as the worsening "kindling effect" observed in the case of alcohol withdrawal (Becker, 1998). In contrast, for those providers who work primarily with nontreatment-seekers who are severely impacted by substance-related harm (e.g., people experiencing homelessness in community-based settings such as shelters), only 5% of whom are interested in abstinence (Fentress et al, 2021), providers must partner with these potential service users ("meet them where they are at") if they hope to be helpful.…”
Section: Limitations On Integrating the Constructs Of Substitute Addi...mentioning
confidence: 99%
“…AI/AN people have reported experiencing structural (e.g., lack of time and transportation) and motivational (e.g., not wanting to stop drinking) barriers to treatment (Haeny et al, 2021; Venner et al, 2012). Research has also highlighted concerns about the cultural acceptability of directive, Western, abstinence‐based approaches and the corresponding need for more research on lower‐barrier, patient‐centered and culturally grounded (i.e., derived from the beliefs and values of a specific culture) AUD treatments (Blume, 2021; Donovan, 2015; Nelson, Collins, et al, 2023; Venner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In phase 1, our research team conducted (a) interviews with 31 urban AI/AN patients with AUD, (b) key informant interviews with six management and traditional health professionals, and (c) five staff and provider focus groups. In these forums, we asked participants about AUD treatment they had experienced or administered to date, suggestions for its revisioning, perceptions of harm reduction, interest in Talking Circles as a means of community‐led and culturally grounded healing, and ideas to tailor the HaRTC and AUD treatment more broadly to meet the needs of AI/AN patients (Nelson et al, 2022; Nelson, Collins et al, 2023).…”
Section: Introductionmentioning
confidence: 99%